Serum Iron and Free Hemoglobin Concentrations in Patients with Acute Ischemia Stroke - Ghadiani, Faezeh -; Qujeq, Durdi; Ahmadi Ahangar, Alijan (Archives of Advances in Biosciences, 2016)
A number of evidences suggest that during ischemic stroke, serum iron and hemoglobin (Hb) levels are changed. Yet, there are few reports in the literature related to this issue and resolution of this mechanism requires further experiments. The aim of the present study was to investigate the potential role of serum iron and hemoglobin levels as a biomarker in diagnosis of acute ischemic stroke. The sample size was 60 ischemic stroke patients who were admitted to the Rouhhani hospital in Babol, with 60 healthy volunteers selected as control group. Clinical evaluation consisted of complete medical history and physical examination and neuro-imaging's studies. Sampling strategy was based on clinical characteristics, including age, gender, and history of diseases. Laboratory measurements were performed in the department of clinical biochemistry. Serum iron and plasma hemoglobin levels were measured by standard kit of iron and hemoglobin ELISA Kit, as of the manufactures' manual. Data were analyzed through statistical software SPSS version 22. The mean level of serum iron and hemoglobin in patients with acute ischemic stroke were higher than those in control group (P<0.05). However, there was no relation between these biomarkers and age and gender of subjects (P>0.05). Our results reinforce the possibility of serum iron and hemoglobin as biomarker in diagnosis of ischemic stroke patients.